Surprises and Dreams: workshop method to co-create community-based transformative knowledge - Rasmus, Sirpa; Sarkki, Simo; Wang, Irina; Burgess, Philip; Habeck, Joachim Otto; Horstkotte, Tim; Jokinen, Mikko; Matthes, Heidrun; Mettiäinen, Ilona; Parviainen, Tuuli; Pekkarinen, Antti-Juhani; Post, Laura; et al. (Routledge, 2025)
Pressing sustainability challenges call for research methodologies that enable co-creation of transformative knowledge that that can catalyse societal and policy change. We introduce a participatory workshop method called ‘Surprises and Dreams’ and demonstrate how it can support the co-creation of systems, normative, and transformative knowledge. The method uses cognitive mapping to explore the current state of the system and potential future disruptions (systems knowledge) and includes steps for eliciting participants’ visions and aspirations (normative knowledge). Taken together this can lead towards creation of transformative knowledge that could contribute to finding acceptable solutions to locally relevant problems. In a case study, we demonstrate the application of the method on the current state and future developments in reindeer husbandry in Fennoscandia. Based on the results, we position the three types of knowledges into a Three Horizons framework and discuss how our method supports identifying and describing transformative knowledge. Our case study responds to a need to understand complex systems and normative and contested future aspirations and to achieve change towards more sustainable solutions. We conclude that our method is a promising co-creation tool, also beyond our case study, in its applicability to comparable situations when community-based knowledge is needed.
Keywords: futures research; participatory workshops; reindeer husbandry; transformative knowledge; three horizons framework